Productive performances and carcase quality of male and female Italian Padovana and Polverara slow-growing chicken breeds. Issue 2 (3rd April 2018) - Tasoniero, Giulia; Cullere, Marco; Baldan, Gabriele; Dalle Zotte, Antonella
Abstract: Live performances and carcase quality of Padovana ( n  = 81) and Polverara ( n  = 76) chickens were investigated considering breed, gender and their interaction (B × G). Birds were reared until 183 d of age. After slaughter, yields were computed, and pH and L*a*b*colour values were measured on breast and leg meat. Breeds exhibited similar performances and yields, except a greater commercial carcase incidence for Polverara ( p  < .01). Breast meat quality was similar, except for higher L * value of Padovana fillets ( p  < .01). Polverara legs exhibited lower pH ( p  < .0001), lower L * value ( p  < .001) and higher a * value ( p  < .0001). Gender influenced performances and carcase quality traits. Males showed heavier live weight ( p  < .0001), carcase weight and cuts ( p  < .0001) and commercial carcase yield ( p  < .05), females displayed greater breast yield ( p  < .0001), whereas net carcase yield (% SW) was similar between sexes. Female fillets showed lower pH ( p  < .001) and higher L * and b * values ( p  < .0001); their legs had also higher L * and b * values ( p  < .0001). On the contrary, male legs were remarkably redder ( p  < .0001). Considering breast meat quality, B × G interaction counterposed Polverara males and Polverara females, whereas the greatest differences in leg meat quality existed between Polverara males and Padovana females. This study revealed that the two breeds and genders possess peculiar quality traits.